Simulation of magneto mixed convective flow and thermal behavior of hybrid nanofluid in a partially heated wavy cavity - Chattopadhyay, Anirban; Malo, Rupchand; Öztop, Hakan Fehmi; Pandit, Swapan K.; Goswami, Krishno D. (Elsevier, 2023)
This study is an attempt to address numerically the thermal performance of magneto mixed convection in a wavy cavity filled with Cu-Al2O3(50%-50%) hybrid nanoparticles suspended in water under the influence of magnetic field dependent viscosity. A focus is made on the nonuniform partial heating from the left. The role of geometric parameters on the thermal performance is scrutinized thoroughly by changing surface waviness of the right wall, heating location and the direction of motion of the top and bottom walls. Based on these lid motion, the analysis is conducted by considering four geometrical set up. The transformed governing Navier- Stokes equations in dimensionless form are written in stream function-vorticity and energy transport equations. These equations are solved by using an inhouse computing code written in the compact finite difference approach. This study encompasses the effects of different physical pertinent parameters such as Richardson number, Hartmann number, magnetic orientation, solid concentrations, magnetic number. Simulations show the significant enhancement of thermal performance with the increase of magnetic orientation, undulation of the waviness and solid concentration of nanoparticles while it decreases with the increase in magnetic intensity. It is also seen that Case-I (single wall motion) and Case-III (parallel wall motion) can be an optimal configuration to get the strongest heat transfer inside the partially heated wavy enclosure.
Keywords: Hybrid nanofluid; Wavy enclosure; Partial heating; Mixed convection; MHD; MFDV; Compact scheme